Comparison of 12-Hour Creatinine Clearance and Estimated Glomerular Filtration Rate in Renal Transplant Recipients. (April 2013) - Kumar, Rakesh; Pendyala, Prashant; Attwood, Kris; Gray, Vanessa; Venuto, Rocco; Tornatore, Kathleen
<x xml:space="preserve">Abstract</x> Glomerular filtration rate (GFR) is an essential clinical assessment of renal function post-renal transplantation. Creatinine clearance (CrCl) measured over 12 h and estimated GFR (e-GFR) (calculated by the Modification of Diet in Renal Disease equation) were compared in 28 stable renal transplant recipients (RTRs). This single center study included 14 African American (AA) and 14 Caucasian (CC) recipients. The 12-h creatinine clearance (CrCl-12 h) was determined by monitored urine collection and by e-GFR on two occasions (two phases) separated by at least 2 weeks. Statistics included mixed model analysis of CrCl-12 h and e-GFR relative to race, phase, and difference between parameters. In the first phase, the e-GFR was higher in AA males (58.4 ± 14.8 mL/min) than the CC males (46.2 ± 10.2 mL/min) (p = 0.032), whereas the CrCl-12 h of AA males (70.8 ± 8.7 mL/min) and CC males (63.3 ± 21.7 mL/min) was not different (p = 0.740). During the second phase, the e-GFR in AA and CC RTRs was 55.4 ± 10.1 mL/min and 47.6 ± 10.7 mL/min (p = 0.117), respectively, whereas CrCl-12 h in AAs was 64.71 ± 17.9 mL/min and in CCs was 62.0 ± 14.9 mL/min (p = 1.000). The CrCl-12 h was higher than the e-GFR (p < 0.001) irrespective of race or phase. CrCl-12 h was not different on both occasions (p = 0.289) in all the patients. CrCl-12 h was consistently greater than e-GFR. The difference between these e-GFR estimates may have an importance in the care of RTRs.